Iatrogenic Cushing's syndrome and adrenal insufficiency in infants on intranasal dexamethasone drops for nasal obstruction – Case series and literature review. (February 2018) - Joshi, Rohan R.; Maresh, Alison
Abstract: The use of intranasal steroid drops for nasal obstruction in infants is common practice and can prevent more invasive surgical procedures; however, it is not without complication. We describe 2 cases of iatrogenic Cushing's secondary to nasal steroids in infants with nasal obstruction, discuss the etiology of this unusual complication, and review previous literature reports. While reporting in the literature is sparse, these cases highlight the risk of development of adrenal insufficiency with usage of nasal steroid drops in infants as well as the need for close monitoring of administration and tapering of the drops. Additionally, we suggest an approach to the infant with symptomatic nasal obstruction that addresses the usage of intranasal steroid drops and emphasizes the need for quick tapering and possible endocrine consultation when appropriate.